PERAN GURU DALAM MEMBENTUK KARAKTER SISWA KELAS IV SD NEGERI 157019 PINANGSORI 12 - Manalu, Eigten Febiola; Ilahi, Afdhal; Batubara, Ulfah Nury; Nurbaiti, Nurbaiti; Safitri, Reviva (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to: 1) determine the character of fourth grade students at SD Negeri 157019 Pinangsori 12, 2) Find out the role of teachers in shaping the character of students at SD Negeri 157019 Pinangsori 12. The method used in this research is a qualitative method with a descriptive approach. Data collection using observation methods, interview methods, and documentation. Meanwhile, data analysis uses descriptive analysis which consists of: data reduction, data presentation and drawing conclusions/verification. The object of this research is the role of teachers in shaping the character of students at SD Negeri 157019 Pinangsori 12. The subjects in the research are the class IV teacher, Study teacher, class IV students. From this research, the following findings were produced: 1) The character of students at SD Negeri 157019 Pinangsori 12 is good, because most students are able to do their own assignments without having to copy their friends, obey the rules, complete assignments well, and have self-confidence and never give up. 2) The role of teachers at SD Negeri 157019 Pinangsori 12 in shaping student character has been carried out by being role models, communicators, motivators, mentors and class managers.